Forensic Accounting Techniques on Fraud Prevention in Tertiary Institutions in Cross River State, Nigeria - Mercy N. G. Akeke; Cletus Akpo Atah (Richtmann Publishing, 2023)
This study examined the influence of forensic accounting techniques on fraud prevention in tertiary institutions in Cross River State, Nigeria. The study's methodology was a survey research design. Two research questions and two null hypotheses were developed in order to fulfill the study's objectives. Due to the manageable size of the population, all 152 auditors in bursary department participated in the study. A questionnaire titled “Forensic Accounting Techniques on Fraud Prevention” (FATFP) with a four-point rating scale was used for data collection. Two specialists in accounting department and one expert in measurement and evaluation validated the instrument. The Cronbach's alpha method was used to calculate the overall reliability coefficient of the instrument, which is.79. The standard deviation and mean were used to answer the research questions. The null hypotheses were tested using an independent t-test at the.05 level of significance. The findings revealed that computer-assisted audit techniques and interview audit techniques had a significant influence on fraud prevention at tertiary institutions. Among other things, it was recommended that, government should arm auditors with information and communication tools to aid auditing procedures for fraud prevention. Once again, auditors should use contemporary interview approaches, including watching candidates during interviews, using recording equipment, and installing CCTV cameras strategically placed to capture correct data that will aid in stopping fraudulent operations in Nigerian educational institutions, particularly in Cross River State, Nigeria. Received: 11 November 2022 / Accepted: 28 December 2022 / Published: 5 January 2023